The Environment and Textile Industry-Friendly Hirsute Cotton Variety, Indica - Sundaramurthy, V. T.; Saxena, Sujata (International Journal of Bio-resource and Stress Management, 2020)
A short statured variety Indica with open type of canopy that matured in 130 days yielded 2246 kg of seed cotton ha-1 with better quality of fibres than the other popular varieties MCU5, MCU5 VT and Surabhi which recorded 6.50 to 12.15% lesser yield in the village farms with lower quality of fibres than Indica. The bleached fibres of variety Indica were brighter white in colour with lower tinge of yellowness than the other varieties. Upon dyeing with a blue and a red reactive dye to 0.5% shade, the uptake of dyes by Indica was more than the other varieties and it left lesser dye in the dye bath irrespective of the dye. The variety MCU 5VT recorded the lowest dye uptake and left more dye residue in the dye bath as compared to the other varieties. The dyed fibres of Indica were darkest in colour with better colour strength than the other varieties which may save some dye costs for the textile industries since a darker colour can be produced with lesser amount of dye. Since Indica left least residual dye, dye effluent from this variety will cause lesser damage to the environment and soil. It may also help the Textile industries to spend less on treatment of dye effluent as lesser quantity of residual dye is likely to be present in it. Use of this cotton variety may thus reduce the overall dyeing costs and make the garments made out of the fibres of this variety to cost less than the other popular cotton varieties.